The Role of Big Data and Blockchain in Decentralized Decision-Making: A Comprehensive Review - Kostopoulos, Nikos; Antonopoulou, Hera (Technium Business and Management, 2024)
This research paper investigates the synergistic role of Big Data and Blockchain in decentralized decision-making processes across a wide ambient of sectors. It goes deep in defining principles, and major characteristics of both technologies underpinning their potential in augmenting autonomy, collaboration, and democratization. The authors review current applications and implications of these technologies in improving traceability, security, and real-time analytics in various industries, such as healthcare, finance, and supply chain management. The paper discusses further emerging trends, challenges, and future directions of big data and blockchain integration, which stress further research and multi-disciplinary collaboration. These results show that the transformative potential of this technology would have a very important effect on the area of decentralized decision-making, elaborating strategic recommendations for organizations and policymakers. A lot of literature and reference reviews justify the conclusions that are drawn in this paper and thus serve as an essential tool to aid further study and innovation in this thriving field.